The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.950440
|View full text |Cite
|
Sign up to set email alerts
|

Impact of entrepreneurial curriculum on entrepreneurial competencies among students: The mediating role of the campus learning environment in higher education

Abstract: This study explored the direct and indirect influences of the entrepreneurial curriculum on entrepreneurial competencies, using the campus learning environment as a mediator. In this study, a survey questionnaire composed of 48 items was used to collect data on the entrepreneurial curriculum, entrepreneurial competencies, and campus learning environment from pre-service vocational teachers enrolled in six universities located in Hunan Province, China. The entrepreneurial curriculum has four components, namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…The findings demonstrated how crucial a role the learning environment plays in helping students build their entrepreneurial skills and competences. These results are consistent with earlier study on the impact of the educational environment on the acquisition of entrepreneurial skills and competencies in students (Iqbal et al, 2022), this study found that most students (>50%) had a modest level of entrepreneurial competency.…”
Section: Discussionsupporting
confidence: 93%
“…The findings demonstrated how crucial a role the learning environment plays in helping students build their entrepreneurial skills and competences. These results are consistent with earlier study on the impact of the educational environment on the acquisition of entrepreneurial skills and competencies in students (Iqbal et al, 2022), this study found that most students (>50%) had a modest level of entrepreneurial competency.…”
Section: Discussionsupporting
confidence: 93%
“…This demonstrates that students nowadays have a mindset of entrepreneurship and have thought about both the advantages and disadvantages of being an entrepreneur. In a similar vein, Iqbal et al (2022) stated in a prior study that having a mindset of entrepreneurship helps students have a better understanding of a variety of outcomes and circumstances that are crucial for entrepreneurial studies.…”
Section: Discussionmentioning
confidence: 88%
“…"The competency approach applied to an entrepreneurial context can be a baseline standard for creating a new venture" (Fragoso, Rocha-Junior, Xavier, 2020, p. 3). Iqbal et al (2022) defined entrepreneurial competencies as "the set of behavioural predispositions that influence students' abilities to succeed in an entrepreneurial venture" (Iqbal et al, 2022). Entrepreneurial competencies is "the overall capability of the entrepreneur to execute a job role successfully" (Al Mamun, Nawi, Shamsudin, 2016).…”
Section: Entrepreneurial Competenciesmentioning
confidence: 99%
“…Assessing the development of students' entrepreneurial competences, skills and intentions, and the relationship between basic entrepreneurial competences that must be developed in an educational context is currently becoming an increasingly important subject of interest, highlighted by many scientists and researchers around the world (Solesvik, Entrepreneurship education is an emerging direction for the development of the entrepreneurial mindset around the world (Iqbal et al, 2022). It is a key factor in the development of a favourable approach to undertaking new ventures.…”
Section: Introductionmentioning
confidence: 99%